"There is not only one mother". Motherhood as shown by the written press and on the web in Argentina (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This article is a first approximation to which the representations of the figure of the mother are, as presented in written discourses made by the press as well as on the web in Argentina. Based on the selected cases – three articles from different newspapers and a web site- we can see these range between the patriarchal reproduction and the good mother heteronormative and the dissenting opinions of cisheteronormative motherhood. We point out that as regards the written press, articles have been selected from newspapers that have values and follow interests of different sectors of society, so they show heterogeneous positions. In addition, the study of Lesmadres on the web is the lengthiest since it states a radical criticism of the supposed heterosexual mother. The analysis shows there are discourses that strengthen the woman mother concept as well as others that question motherhood as a universal experience in the case of a heterosexual couple, and thus the concept of family as a unit of reproduction.
Keywords: motherhood; representations; discourses; dissidence; gender